Diagnosis and Detection of the Main Bacterial Pathogens of Stone Fruit and Almond - López, María M.; Roselló, Montserrat; Palacio-Bielsa, Ana (2017)
Diagnosis and detection are key aspects related to plant health status. A critical review of the available diagnostic methods utilised for Agrobacterium rhizogenes and A. tumefaciens, Pseudomonas amygdali, P syringae pv. mors-prunorum, P syringae pv. persicae, P. syringae pv. syringae and Xanthomonas arboricola pv. pruni, the main pathogens of the stone fruit trees, is presented. As there is a general lack of updated standardized protocols for the detection of most of these bacteria, the most appropriate media for their isolation are reported along with serological reagents, PCR and real-time PCR protocols with comments on their accuracy for the analysis of these pathogens in plant samples. There are many selective media for isolation, especially for Agrobacterium spp., but fewer for Pseudomonas spp. and X. arboricola pv. pruni. Serological techniques are not: very useful for these pathogens due to the current lack of specific antibodies commercially available. As to molecular methods, it is surprising to find so many PCR protocols for Agrobacterium species, very few and unspecific for the Pseudomonas species pathogenic to stone fruit trees, and several recent PCR protocols for X. arboricola pv. pruni. The new advances in genomics and proteomics will provide information for selecting new targets to develop specific and sensitive techniques for the diagnosis and detection of these bacterial pathogens in plant material.